Unveiling the Electrocatalytic Performances of the Pd-MoS2 Catalyst for Methanol-Mediated Overall Water Splitting - Aviraj M. Teli; Sagar M. Mane; Rajneesh Kumar Mishra; Wookhee Jeon; Jae Cheol Shin (Inorganics, 2025)
Herein, this work elucidates the synthesis of the Pd-MoS2 catalyst for application in methanol-mediated overall water splitting. The scanning electron microscope (SEM) and transmission electron microscope (TEM) pictures offer an exciting nanostructured shape of the Pd-MoS2, depicting a high surface area. Further, high-resolution TEM (HRTEM) pictures confirm the lattice plane (100), lattice spacing (0.26 nm), and hexagonal crystal structure of the Pd-MoS2. Moreover, high-angle annular dark-field (HAADF) images and related color maps disclose the Mo, S, and Pd elements of the Pd-MoS2. The Pd-MoS2 catalyst exhibits lower overpotentials of 224.6 mV [methanol-mediated hydrogen evolution reaction (MM-HER)] at −10 mA cm−2 and 133 mV [methanol-mediated oxygen evolution reaction (MM-OER)] at 10 mA cm−2. Further, the Pd-MoS2 illustrates noteworthy stability for 15.5 h for MM-HER and 18 h for MM-OER by chronopotentiometry test. Excitingly, the Pd-MoS2∥Pd-MoS2 cell reveals a small potential of 1.581 V compared to the MoS2∥MoS2 cell (1.648 V) in methanol-mediated overall water splitting. In addition, the Pd-MoS2∥Pd-MoS2 combination reveals brilliant durability over 18 h at 10 mA cm−2.